Effect of different concentrations of ortho-phthalaldehyde on biofilms formed by Pseudomonas fluorescens under different flow conditions - Simões, M. (2003)
The effectiveness of different concentrations of orthophthalaldehyde (OPA) in controlling biofilms of Pseudomonas fluorescens formed on stainless steel slides, using flow cell reactors under laminar and turbulent flow, was investigated by determining the variation in mass and respiratory activity. The physical stability of the biofilm with and without exposure to OPA was studied in a rotating device as variation in the mass of the biofilm on the surface after exposure to different rotation velocities. The activity of OPA against bacterial suspended cultures was evaluated in the presence and absence of bovine serum albumin (BSA) in order to evaluate the interference of proteins on the activity of the biocide. The results showed that biofilms formed under different flow conditions had different properties and reacted differently after biocide application. Biofilms formed under laminar flow were more easily inactivated than those formed under turbulent conditions. However, OPA did not promote the detachment of biofilms from the surface. The exposure of biofilms to different shear stress conditions after OPA treatment enhanced removal from the surface, indicating that OPA may weaken the biofilm matrix. The biocide was more effective on suspended cells than on cells grown in biofilms. This fact may be explained by the reaction of the biocide with proteins of the polymeric matrix of the biofilm as suggested by the significant reduction of biocide action on suspended cells in the presence of BSA.